The Impact of Human Resources Information Systems and Internal Control on Employee Performance at PT. Sinar Artha Semesta - Khoirunnisa, Amalia; Murniadi, Murniadi; Zatira, Dhea (Green Publisher Indonesia, 2025)
The purpose of this study was to determine the impact of Human Resources Information Systems and Internal Control on Employee Performance at PT Sinar Artha Semesta partially and simultaneously. Using associative methods with a quantitative approach. 83 people were sampled. Data collection techniques and tools are questionnaires or questionnaires. Based on the tcount value of 7.644> ttable 1.663, Hα is accepted with a sig of 0.04 < α 0.05 and a statistical F value of 40.084> F table 3.110 the decision is Ha is accepted. The results showed that 1.) Human Resources Information System has a positive and significant impact on Employee Performance; 2.) Internal Control has a positive and significant impact on Employee Performance; 3.) Human Resources Information System and Internal Control simultaneously have a positive and significant impact on Employee Performance. In addition, it has a contribution of 50.1% while the rest is influenced by other variables not examined.